Ethics Analysis In Public Service To Support Good Governance : A Case Study Of ASN At The Tanjungbatu Lurah Office, Riau Islands City: Analisis Etika Dalam Pelayanan Publik Untuk Mendukung Good Governance : Studi Kasus ASN Di Kantor Lurah Tanjungbatu Kota Kepulauan Riau - Lisa Larasaty; Nilman Ghofur (Gayaku Publisher, 2025)
Ethics is an important foundation for State Civil Apparatus (ASN) in carrying out their role as public servants. By implementing good ethics, ASN is expected to provide public services with integrity, transparency, and a focus on the public interest. This study aims to evaluate how ASN ethics are applied in public services and their role in creating Good Governance at the Tanjungbatu City Village Office, Karimun Regacy. The method used is descriptive qualitative, with data collection conducted through in-depth interviews, field obseravtions, and literature reviews from relevant journals and e-books. The results show that most ASN have implemented ethical values such as honesty, responsibility, and professionalism in carrying out their duties. However, there are still obstacles such as lack of discipline weak internal supervision, and limitations in human resources. Overall, the implementation of ASN ethics at the Tanjungbatu City Village Office has been running quite well and supports the principles of Good Governance, although there are still improvements in terms of consistency and fostering work ethics.